2017
DOI: 10.1063/1.4982589
|View full text |Cite
|
Sign up to set email alerts
|

Unusual magnetic transition near metal-insulator transition and paramagnetic anomaly in VO2

Abstract: Experiments for vanadium dioxide show a magnetic transition characterized by a sharp variation in susceptibility associated with the metal-insulator transition at the temperature Tc. The sample is shown to be of Pauli paramagnetism above Tc but of anomalous paramagnetism below Tc. Considering co-contributions of Pauli paramagnetism of residual V4+ ions and Curie-like paramagnetism of V-V dimers, we propose a phenomenological expression for the temperature-dependent susceptibility below Tc, which yields an exce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…The VO 2 is of paramagnetism for the whole range of temperature covering from high- T metallic to low- T insulating states, which can be confirmed through the measurement of hysteresis loop in which no magnetic hysteresis becomes visible at various fixed temperatures from 370 K to 10 K 28 . Nevertheless, the experimental fact of magnetic transition displayed in Fig.…”
Section: Resultsmentioning
confidence: 62%
See 1 more Smart Citation
“…The VO 2 is of paramagnetism for the whole range of temperature covering from high- T metallic to low- T insulating states, which can be confirmed through the measurement of hysteresis loop in which no magnetic hysteresis becomes visible at various fixed temperatures from 370 K to 10 K 28 . Nevertheless, the experimental fact of magnetic transition displayed in Fig.…”
Section: Resultsmentioning
confidence: 62%
“…Below T m,offset the dimers are formed by spin pairing of adjacent V 4+ ions in antiparallel, so that each dimer has no magnetic moment. Therefore, the dimers cannot contribute to the observed low- T paramagnetism, unless that each dimer is phenomenologically assumed to be formed by spin pairing of two V 4+ ions at a T -dependent angle 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Above T N , their relatively weak magnetism is constant with temperature and is attributed to Pauli paramagnetism. 5 Below T N, some recent studies have suggested the possibility of the coexistence of a weak Curie-Weiss paramagnetic behavior with the AF order, such as in strained or doped bulk VO 2 6-8 or V 2 O 3 films and nanoparticles. 9 A ferromagnetic signature was even assumed in some cases, such as VO x nanotubes, [10][11][12] whose origins remain unexplained.…”
mentioning
confidence: 99%
“…The paired V-V dimers that are formed as zigzag chains arranged in an approaching antiparallel direction, approximately contributing a zero magnetic moment. Besides the paired V-V dimers, some unpaired free V 4+ ions may also be present in the monoclinic [36]. For Zr doped VO 2 samples, the total magnetic moment is given by M total = M dimers + M free + M Zr .…”
Section: Resultsmentioning
confidence: 99%